Sequence Variation of Melanocortin 1 Receptor (MC1R) Gene and Association with Plumage Color in Domestic Geese - Jing Huang; Bing Zhou; Da-Qian He; Shi-Yi Chen; Qing Zhu; Yong-Gang Yao; Yi-Ping Liu (The Journal of Poultry Science, 2014)
In contrast to other domestic and wild animals, the genetic variation of MC1R gene and association with plumage color has not been investigated in domestic goose. In the present study, we sequenced 714 bp fragment of the MC1R for 176 individuals from two goose breeds with three plumage color pattern (Landes goose, gray plumage, n＝58; Landes goose, spotted plumage, near black, n＝36; Zhedong White Goose, white plumage, n＝82). A total of five single nucleotide polymorphisms (SNPs) were detected, including c.210C>T, c.321C>T, c.411C>T, c.525C>T, and c.756G>A, which subsequently determined seven haplotypes (H1-H7). Among them, H2 and H4 were the predominant haplotypes. Association analysis revealed that haplotypes H2 and H5 were significantly associated with white plumage of Zhedong white goose, whereas H3 was significantly associated with gray plumage in Landes goose (p<0.01). Diplotypes H2H2 and H3H4 were associated with white plumage in Zhedong white goose and gray plumage in Landes goose (p<0.01), respectively. The results suggested that the genetic variation of MC1R is also significantly associated with the plumage color in domestic goose.